The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1172/jci109470
|View full text |Cite
|
Sign up to set email alerts
|

Chick embryo pancreatic transplants reverse experimental diabetes of rats.

Abstract: A B S T R A C T The effectiveness of xenogeneic embryonic tissue in the treatment of experimental diabetes has been investigated in rats. The splenic lobes (80) of 15-to 18d-old chick embryos, composed almost exclusively of endocrine tissue, were implanted directly into the hepatic parenchyma of the rat recipient. The biochemical and metabolic changes in the recipients suggest that embryonic transplants of 15-d-old chick pancreases were able to significantly improve, for a prolonged period of time (18 mo), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
(33 reference statements)
6
21
1
Order By: Relevance
“…It is possible that xenotransplantation of fetal pancreas is particularly suited to induction of tolerance. However, neither Eloy et al 20 nor Abraham et al 21 nor we 3,10-13 define an immunological mechanism.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…It is possible that xenotransplantation of fetal pancreas is particularly suited to induction of tolerance. However, neither Eloy et al 20 nor Abraham et al 21 nor we 3,10-13 define an immunological mechanism.…”
mentioning
confidence: 59%
“…Eloy et al described normalization of glucose post-transplantation of E15, but not E18 embryonic chick pancreas into non-immmune suppressed STZ-diabetic immune competent rats. 20 Abraham et al 21 described successful xenoengraftment in multiple organs of human pancreatic islet-derived progenitor cells infused in non-immunosuppressed immune competent mice. It is possible that xenotransplantation of fetal pancreas is particularly suited to induction of tolerance.…”
mentioning
confidence: 99%
“…Eloy et al [253] found that islet rich, 15 day (but not 18 day) chick embryo pancreas significantly improved diabetes in rats after direct injection into the hepatic parenchyma. Except for this report, discordant xenografts have been successfully transplanted only under very special circumstances, to thymic aplastic mutant nude (nu/nu) mice or nude (rnu/rnu) rats, which are genetically unable to reject allo-and xenografts [254,255].…”
Section: Islet Xenografts If Rejection Of Tissue Transplanted Frommentioning
confidence: 99%
“…1 Cell therapy has since grown rapidly by nonhomogenous cell therapy from chick embryo pancreatic transplant, which reversed experimental diabetes in rats. 2 Mario Capecchi, Martin Evans, and Oliver Smithies received the 2007 Nobel Prize in Physiology or Medicine for work going back to 1981 on development of mouse embryonic stem cell technology that allowed any gene to be "knocked out" in mice. 3 In 1998, Thomson and associates adapted the mouse techniques to human blastocysts, showing for the first time that human stem cells could be established.…”
Section: Introductionmentioning
confidence: 99%